The role of the general election commission to increase community political participation in the 2020 general election of Medan city - Harefa, Rifail Khair; Adhani, Abrar (Universitas Ahmad Dahlan, 2021)
This study aims to determine the role of the general election commission in increasing public participation in the 2020 elections for Medan City. The method used in this research is qualitative. The informants in this study were members of the Medan City Election Commission and the public who were registered as the final voter list in the 2020 Medan City Election. The results of the study can be seen that the role that the Medan City KPU has to foster community participation in politics, especially in the Medan City elections from the KPU regarding the implementation schedule, registration, and voter data collection. Then socialization with face-to-face communication through mass media, social media, creative media, KPU announcement boards, and so on.